Maquiladoras and market mamas: women's work and childcare in Guatemala City and Accra - Quisumbing, Agnes R.; Hallman, Kelly; Ruel, Marie T. (International Food Policy Research Institute, 2003)
This study analyzes work, childcare arrangements, and earnings of mothers in the poor neighborhoods of Guatemala City and Greater Accra, Ghana, two urban areas where formal- and informal-sector work differ in importance. Unlike previous studies on childcare that take mother's work status as given, this paper treats childcare choice and labor force participation of women as joint decisions. Our empirical results indicate that participation in the labor market and use of formal day care are, in fact, jointly determined. In both Guatemala and Accra, life cycle and household demographic factors, notably child age, appear to have important effects on both decisions. In both cities, higher household wealth reduces the mothers' chances of working, presumably via an income effect. Controlling for endogeneity of labor market participation and formal day-care use, in Guatemala, day-care prices do not have significant impacts on earnings; neither does the number of day-care centers within a 10-minute walk affect earnings in Accra. In Guatemala, maternal education is an important determinant of utilization of formal day care, but does not have large effects on whether she works for pay or not. In contrast, in Accra, maternal education does not affect either the demand for formal care or the decision to work. In Guatemala, greater travel time from home to the day-care center reduces utilization of this type of care, but a larger supply of day-care centers in the community does not affect use of formal care in Accra. The lack of importance of formal day-care supply variables in Accra -- compared to the effect of some variables such as travel time to day-care centers in Guatemala -- suggests that provision of formal day care may not be as critical an intervention to increase mothers' labor force participation rates in cities where the informal sector dominates, such as in Accra. In more urbanized settings like Guatemala City, where the formal sector generates a higher proportion of jobs for women, formal day care is more important to mothers' decision to work. -- Author's Abstract